Stemming the tide of mental health problems in young people: Challenges and potential solutions. (April 2023) - Eapen, Valsamma; Stylianakis, Anthea; Scott, Elizabeth; Milroy, Helen; Bowden, Michael; Haslam, Ric; Stathis, Stephen
One in five people experience clinically relevant mental health problems before the age of 25 years. Furthermore, in Australia, one in seven children are reported to experience a mental health disorder. Consequently, there has been a steady increase in demand for mental health services for children and young people, and this has been compounded by the COVID-19 pandemic. Unfortunately, currently many children and young people with mental health difficulties are not accessing appropriate and/or timely care, with individuals and families finding it increasingly difficult to access and navigate suitable services. In part, this is related to the fragmented and isolated manner in which child mental health services are operating. To address the current issues in access to appropriate child and adolescent mental health care in Australia, a novel Integrated Continuum of Connect and Care model is proposed to integrate relevant services along a tiered care pathway. The aim of this model is to facilitate timely access to mental health services that meet the specific needs of each child/young person and their family. This model will function within co-located service hubs that integrate health care through a comprehensive assessment followed by a link up to relevant services. The Integrated Continuum of Connect and Care has the potential to pave the way for unifying the fragmented child and youth mental health system in Australia.